The effectiveness of Regulation FD - Gintschel, Andreas; Markov, Stanimir (Journal of Accounting and Economics, 2004)
We examine whether Regulation Fair Disclosure (Reg FD) has reduced the informativeness of analysts’ information outputs. For a sample of financial analysts’ earnings forecasts and recommendations released in a 2-year window around Reg FD's effective date, we show that in the post-Regulation FD period the absolute price impact of information disseminated by financial analysts is lower by 28%. We also show that the drop in price impact varies systematically with brokerage house and stock characteristics related to the level of selective disclosure prior to Reg FD. Based on the time-series and cross-sectional evidence we conclude that Reg FD has been effective in curtailing selective disclosure.